Soil microorganisms and plant diseases associated to cocoa (Theobroma cacao L.) genotypes in the Ecuadorian Amazon (2018)
The aim of this research was to analyze the relationship between soil microorganisms and the major diseases affecting promising clones of cocoa (Theobroma cacao L.) in the Ecuadorian Amazon. The EET-95, EET-96, EET-103 and CCN-51 clones were evaluated, respectively, the latter used as a control, for this, the amount of bacteria, fungi and total actinomycetes, expressed in colony forming units (CFU) per soil gram, was determined, present in the soil rhizosphere of the three cocoa clones, as well as the appearance of the major plant diseases which attacks the cocoa crop. Data were statistically analyzed by one-way ANOVA and Tukey HSD test p≤0.05. The bacteria were the microorganisms with the greatest association to the evaluated cocoa clones in this study, followed by actinomycetes and fungi. Clone CCN-51 had achieved the highest number of bacteria, clones EET-96 and EET-103, had achieved a higher incidence of actinomycetes and clone EET-103, the greater presence of parasitic fungi. The witch broom disease, whose causative agent is Cripinellis perniciosa Sthael Singer., affected to a lesser extent the EET-103 and CCN-51 clones, while frosty pod rot caused by the parasitic fungus Moniliophthora roreri (Cif and Par) Evans et al., showed the EET-103 clone with the highest incidence of this disease and conversely to the CCN-51 clone with the lowest incidence of this pathogen.